INTEGRATING THE FOUR GHARAVASA DHAMMA TO PROMOTE SUSTAINABLE COMMUNITY LEARNING IN THE CONTEXT OF ETHNIC GROUPS IN RATCHABURI PROVINCE - Krudnak, Narisara; Charoenlak, Nipawan; Rueangsri, Wongsiri; Charoenlak, Pakporn (Journal of Buddhist Anthropology, 2025)
Background and Objectives: Applying the FOUR GHARAVASA DHAMMA to daily life in the community of Ratchaburi Province can strengthen morality and society sustainably. The FOUR GHARAVASA DHAMMA consisted of: Sacca (Truthfulness), Tama (Self-Command), Khanti (Patience), and Càga (Generosity). Each of these FOUR GHARAVASA DHAMMA played a vital role in fostering peace in both individual lives and the community. This research aimed to study the integration of the FOUR GHARAVASA DHAMMA, to examine the promotion of sustainable community learning within the ethnic group context of Ratchaburi Province, and to propose the promotion of sustainable community learning based on Buddhist principles in the context of ethnic groups. Methodology: The research employed a mixed methods approach. In the quantitative study, the research instrument used was a five-point Likert scale questionnaire with a reliability coefficient of 0.86. The population consisted of 360 individuals, with a sample group of 186 participants, determined by comparing the sample size using the Krejcie and Morgan table. The statistical methods used in the research included mean, standard deviation, and Pearson's correlation coefficient. In the qualitative study, focus group discussions were conducted, and the instrument used was a semi-structured interview. The key informants included community leaders and local scholars, totaling 18 individuals, selected purposively based on specific criteria. Data was analyzed through content analysis, and the findings were validated using the triangulation technique involving data, the researcher, and the theory. The results were presented descriptively in line with the research objectives. Main Results: The research Founded that: 1) The integration of the Four Gharavasa Dhamma to promote sustainable community learning in the context of ethnic groups in Ratchaburi Province was found to be at a high level ( = 4.56, S.D. = 0.21); and 2) The promotion of sustainable community learning based on Buddhist principles in the context of ethnic groups consisted of: 2.1) Promoting morality and ethics based on the community's social and cultural foundation; 2.2) Learning from real-life experiences; 2.3) Self-reliance according to the philosophy of sufficiency economy; 2.4) Promoting volunteerism; and 2.5) Preserving the community's culture. Involvement to Buddhadhamma: The application of Buddhist principles in local community development helped foster virtues such as honesty, responsibility, and mutual assistance. It focused on enabling the community to live sustainably based on their own cultural identity. Promoting learning according to Buddhist teachings contributed to the development of the community in areas such as education, economy, and society, particularly within the ethnic groups of Ratchaburi Province who preserved their cultural heritage. Conclusions: This research aimed to enhance the potential of the Ratchaburi community by integrating the Four Gharavasa Dhamma: Sacca (Truthfulness), Tama (Self-Command), Khanti (Patience), and Càga (Generosity), to promote sustainable learning within the community in the context of ethnic groups. The focus was on using these principles in community management to strengthen morality and ethics, utilizing technology in teaching and learning, promoting lifelong learning, encouraging participation in decision-making, and adapting to changes. This approach led to the sustainability and overall strength of the community and contributed to peaceful coexistence.